2013
DOI: 10.1111/wbm.12016
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of acetolactate synthase from sulfonylurea herbicide‐resistant Schoenoplectus juncoides

Abstract: Ten accessions of sulfonylurea‐resistant Schoenoplectus juncoides were collected from paddy fields in Japan. In order to characterize acetolactate synthase from sulfonylurea‐resistant S. juncoides, acetolactate synthase amino acid substitutions, whole‐plant growth inhibition and acetolactate synthase enzyme inhibition were examined. Schoenoplectus juncoides has two acetolactate synthase genes (ALS1 and ALS2). The sulfonylurea‐resistant accessions harbored amino acid substitutions at Pro197 or Trp574 in either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…The data of whole-plant response experiments was converted into the percentage of control and subjected to a non-linear regression analysis using GraphPad Software (v.5.0) 31 , 32 . In this study, two AHAS isozymes with different sensitivities to tribenuron-methyl were confirmed to coexist in all R (pHB8, pHB22, pHB23, pHB24, pHB25 and pHB42) subpopulations.…”
Section: Methodsmentioning
confidence: 99%
“…The data of whole-plant response experiments was converted into the percentage of control and subjected to a non-linear regression analysis using GraphPad Software (v.5.0) 31 , 32 . In this study, two AHAS isozymes with different sensitivities to tribenuron-methyl were confirmed to coexist in all R (pHB8, pHB22, pHB23, pHB24, pHB25 and pHB42) subpopulations.…”
Section: Methodsmentioning
confidence: 99%
“…The data obtained from whole-plant response experiments and the in vitro AHAS assay were converted into percentages of the control and subjected to a nonlinear regression analysis using GraphPad Software (v.5.0) 31,32 . In this study, two AHAS isozymes with different sensitivities to tribenuron-methyl were confirmed to coexist in all R (pHB8, pHB22, pHB23, pHB24, pHB25 and pHB42) subpopulations.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…But, there was little information about how the enzymatic resistance profiles relate to specific ALS mutations. Recently Yamato et al () investigated the in vitro dose–response of ALS to imazosulfuron, using ALS enzymes that were extracted from various SU‐resistant S. juncoides accessions (all homozygous) (Table ).…”
Section: Enzymatic Resistance Profilesmentioning
confidence: 99%
“…Data are the results of regression analyses using the formula, y = s × f ( x ) + (1 − s ) × g ( x ). See the text for details and Yamato et al ().…”
Section: Enzymatic Resistance Profilesmentioning
confidence: 99%
See 1 more Smart Citation